1989
DOI: 10.1152/jn.1989.62.6.1201
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for muscle activation during isometric torque generation at the human elbow

Abstract: 1. We studied the patterns of electromyographic (EMG) activity in elbow muscles of 14 normal human subjects. The activity of five muscles that act in flexion-extension and forearm supination-pronation was simultaneously recorded during isometric voluntary torque generation, in which torques generated in a plane orthogonal to the long axis of the forearm were voluntarily coupled with torques generated about the long axis of the forearm (i.e., supination-pronation). 2. When forearm supination torques were superi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
0
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(131 citation statements)
references
References 0 publications
8
110
0
4
Order By: Relevance
“…The obviously not perfect match between EMG and force ( Fig. 2) might to a part be due to the mechanical output of the remaining muscles crossing the elbow (Buchanan et al, 1989). However, when force estimates of the BB improve, this should yield a closer correspondence with the total elbow flexion force as well, given the large contribution of BB to elbow flexion force (Kawakami et al, 1994).…”
Section: Limitationsmentioning
confidence: 95%
“…The obviously not perfect match between EMG and force ( Fig. 2) might to a part be due to the mechanical output of the remaining muscles crossing the elbow (Buchanan et al, 1989). However, when force estimates of the BB improve, this should yield a closer correspondence with the total elbow flexion force as well, given the large contribution of BB to elbow flexion force (Kawakami et al, 1994).…”
Section: Limitationsmentioning
confidence: 95%
“…Earlier studies have suggested the mechanical advantage hypothesis (Buchanan et al 1989;Prilutsky 2000;Zatsiorsky et al 2002;Shim et al 2004a), which states that effectors (muscles or digits) with longer lever arms contribute more to the total rotational action as compared to effectors with shorter lever arms. In our study, two fingers (I and M) produced PR moments (M PR ) while two other fingers (R and L) produced SU moments (M SU ).…”
Section: Moment Production By Individual Fingersmentioning
confidence: 99%
“…According to the mechanical advantage hypothesis (Buchanan et al 1989;Prilutsky 2000;Zatsiorsky et al 2002), these fingers were expected to produce most of the moment in PR and SU, respectively. This was indeed true.…”
Section: Rotational Efforts Into Pronation and Supinationmentioning
confidence: 99%
“…Buchanon 24 suggests that multi-articular muscles are so complex that only one optimal pattern of recruitment exists that provides maximum force yet requires minimal energy expenditure and tissue strain. Karst and Hasan 25 propose that the muscle activation patterns can be predicted using only a few simple variables, such as initial and ®nal joint angels for a given movement.…”
Section: Theoretical Considerationsmentioning
confidence: 99%